MODEL INTEROPERABILITAS ANTAR APLIKASI E-GOV - Sutanta, Edhy (IST AKPRIND Yogyakarta, 2012)
Interoperability between information systems is an urgent problem to be solved in the development of e-Gov in Indonesia. This is caused by the need for increasing the data multisectoral policy-making in order to solve problems involving data from the interrelated sectors. While the state government application in the current environment, are still largely sectoral, in isolation, can not communicate with each other, and heterogeneous. Interoperability between e-Gov applications become important things to be sought the solution to the problem of developing e-Gov in Indonesia are not protracted. This paper is a review of the literature reveals the development of e-Gov in Indonesia, the interoperability problems encountered, and how the model of interoperability between e-Gov built to implement a web services models.